Integrating Sunday with Monday through Friday-Consistencies Between Biblical Principles and Management Theory - Holt, M. Kenneth; Holbrook, Robert L. (Journal of Commerce and Trade, 2014)
Christianity often takes a back seat to secular pursuits rather than serving as the context from which these pursuits originate. In other words, we behave much differently Monday through Friday than we do on Sunday. Part of the problem is that we as Christians sometimes fail to see the interconnectedness of our work and our faith. We know what the Bible teaches about how we should conduct ourselves, and we know what management theorists have said about how we should conduct our business. Specific theoretical and conceptual models firmly rooted in biblical principles are needed to demonstrate how Christian principles are consistent with many existing management theories. This paper takes the reader through Hind’s (1989) “Commandments of Caring,” which formed his basis for Servant Leadership, to show how these biblically derived principles can be found in existing secular management theories. Theories discussed include Taylor’s Scientific Management, House’s Path-Goal Theory, Hersey & Blanchard’s Situational Leadership and several others.